ANALISIS PENGARUH PRAKTIK-PRAKTIK KEPEMIMPINAN TERHADAP KEPUASAN KERJA PEGAWAI UNIVERSITAS BATANGHARI JAMBI - Said Almaududi (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
This research analyzed the influence of the dimensions of leadership practices on employee job satisfaction. Object of this study is the University of Batanghari Jambi. Research problem refers to the phenomenon of data at the University of  Batanghari Jambi, which is indicated by the number of employees in and out within the last 3 years, as well as some of the complaints are often perceived by employees. The problem that arises is: whether the dimensions of leadership practices have an influence on employee job satisfaction.The study used 80 respondents and all respondents were employee University of  Batanghari Jambi. Multiple Regression Analysis.The results of this study indicate that such practices are leadership dimensions and dimension empower others encourage both partial and simultaneous positive effect on employee job satisfaction University of Batanghari.Keywords: Leadership Practices and Job Satisfaction